Stalin era intellectuals
1 online resource.
Keywords: "This book focuses on the extent to which Soviet scholars and cultural theoreticians were able to act autonomously during the Stalin era. The authors question how we should consider certain intellectual achievements which took place despite the pressure of Stalinism, and how best to recognise and describe such achievements. The chapters offer suggestions for new interpretations on Soviet philosophy of science and humanities, linguistics, philosophy, musicology, literature and mathematics from the point of view of general cultural theory. In this way, they challenge the received image of the Stalin-era humanities which reduces them into mere propaganda. Intended for scholars of Russian and Soviet studies this book will dispel many received views about the character of Stalinism and Soviet culture"--